2022
DOI: 10.1101/2022.07.17.22277721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple SEIR-V model to estimate COVID-19 prevalence and predict SARS-CoV-2 transmission using wastewater-based surveillance data

Abstract: Wastewater-based surveillance (WBS) has been widely used as a public health tool to monitor SARS-CoV-2 transmission. However, epidemiological inference from WBS data remains understudied and limits its application. In this study, we have established a quantitative framework to estimate COVID-19 prevalence and predict SARS-CoV-2 transmission through integrating WBS data into an SEIR-V model. We conceptually divide the individual-level viral shedding course into exposed, infectious, and recovery phases as an ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…25 Despite potential bias introduced by using the wastewater data to inform the parameterization of those data in the model, the additive and substitutive power in this study were not very strong, when compared with a preprint study in nowcasting SARS-CoV-2 infections in the Boston metropolitan area, covering a much larger population. 13 This further supports the need for future research into the conditions required for using wastewater data in infectious disease nowcasting. Finally, our models included a simple linear relationship between wastewater data and modeled infections.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…25 Despite potential bias introduced by using the wastewater data to inform the parameterization of those data in the model, the additive and substitutive power in this study were not very strong, when compared with a preprint study in nowcasting SARS-CoV-2 infections in the Boston metropolitan area, covering a much larger population. 13 This further supports the need for future research into the conditions required for using wastewater data in infectious disease nowcasting. Finally, our models included a simple linear relationship between wastewater data and modeled infections.…”
Section: Discussionmentioning
confidence: 61%
“…[9][10][11] Wastewater data has been used in nowcasts of large metropolitan areas, and it has been found that there is no definitive agreement on a case count to water concentration. 8,[12][13][14] Nevertheless, WBE for surveillance has its own unique challenges, including variation in sampling and quantification methods, and challenges mapping wastewater levels to estimates of local disease burden. [15][16][17] As a result, the value of wastewater data for nowcasting disease transmission in subpopulations in addition to, or instead of, traditional surveillance data remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic models have been applied to wastewater data in recent studies, with the primary aim of evaluating the predictive ability of models [ 18 , 19 ] or monitoring growth trends by computing effective reproduction numbers [ 20 , 21 ]. Yet, another important component, scenario modelling, has not been thoroughly explored in combination with wastewater surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we need to exploit wastewater data and incorporate current transmission mechanisms, e.g. repeated infections related to emerging variants and waning immunity, which have not been explicitly captured in previous work [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic models have been applied to wastewater data in recent studies, with the primary aim of evaluating the predictive ability of models [18,19] or monitoring growth trends by computing effective reproduction numbers [20,21]. Yet, another important component, scenario modelling, has not been thoroughly explored in the combination of wastewater surveillance.…”
Section: Introductionmentioning
confidence: 99%